Grammarly as a Computer-Mediated Tool for Enhancing Writing Instruction - Magadan, Crison T.; Tulud, Donnie M. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research explores the impact of Grammarly as a computer-mediated instruction tool, on the academic writing skills of Senior High School students in the Philippines. Methodology: A quasi-experimental research design was used, involving 44 Grade 11 students. Participants were randomly assigned to either an experimental group which received instruction via Grammarly and a control group which followed traditional teaching writing methods. Both groups completed a pretest and posttest thru writing a descriptive essay and a 100-item achievement test. Main Findings: The results showed that Grammarly significantly improved the writing performance and overall achievement of the experimental group, with their mean scores surpassing those of the control group. The findings suggest that integrating Grammarly into writing instruction can positively influence student performance. Novelty/Originality of this study: This study provides valuable insights into both lecturers and students by investigating how feedback and evaluation processes facilitated by Grammarly impact the quality and development of academic essays, the study highlights the tool's potential to enhance the writing process. Specifically, it examines the effectiveness of real-time corrections, suggestions, and feedback provided by Grammarly in helping students improve their writing skills.